1989
DOI: 10.1001/archotol.1989.01860310042019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Labyrinthine Fistula

Abstract: \s=b\This cholesteatoma series comprises 84 ears, 81 of which had a labyrinthine fistula and 3 a horizontal semicircular canal opening that arose as a surgical complication. In 49 ears (58.3%), the operation was a primary one; in 35 ears (41.7%), it was a revision. Of all ears, 21 (25%) were deaf preoperatively. The fistula was located in the horizontal canal in 76 ears (90.4%).The matrix was removed in all these ears, and the fistula was covered with fibrin glue and fascia or periosteum. Hearing was preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
1
8

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 13 publications
10
77
1
8
Order By: Relevance
“…The merits and demerits of canal wall up or down mastoidectomy are also topics of debate. Palve et al [3] suggested that canal wall down mastoidectomy be used for a labyrinthine fistula and Sanna et al [4] favoured consideration of canal wall down mastoidectomy for only a hearing ear, for multiple fistulas, and for revision surgery. Smyth et al [16] described the efficacy of the canal wall down technique for cholesteatoma with labyrinthine fistula, and found that the recurrence rate of cholesteatoma for the canal wall down technique was lower than that for the canal wall up technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The merits and demerits of canal wall up or down mastoidectomy are also topics of debate. Palve et al [3] suggested that canal wall down mastoidectomy be used for a labyrinthine fistula and Sanna et al [4] favoured consideration of canal wall down mastoidectomy for only a hearing ear, for multiple fistulas, and for revision surgery. Smyth et al [16] described the efficacy of the canal wall down technique for cholesteatoma with labyrinthine fistula, and found that the recurrence rate of cholesteatoma for the canal wall down technique was lower than that for the canal wall up technique.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have tried to repair a labyrinthine fistula completely at the time of surgery [3] and have tried to remove the secondary at the time of surgery to leave part of the cholesteatoma matrix [4,5] . Dornhoffer et al [6] have reported that a transvenous corticosteroid injection just before removal of the cholesteatoma matrix is effective at conserving hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Auch ein intraoperativer Perilymphabfluss führt nicht notwendigerweise zur Ertaubung; je nach Ausdehnung kommt es in 5-35% zur Hör-verschlechterung bis zur Ertaubung [6,7,13,14,15,16]. Die operative Technik zur Behandlung eines Cholesteatoms mit Labyrinthfistel wird weiterhin kontrovers diskutiert.…”
Section: Schlüsselwörterunclassified
“…Einige Autoren empfehlen einen Anteil des Cholesteatoms über der Fistel zu belassen [4,14], andere raten, abhängig vom Ausmaß der Fistel, das Cholesteatom komplett zu entfernen [6]. Eine weitere Methode besteht darin, den Anteil des Cholesteatoms über der Fistel zweizeitig zu entfernen [15,16].Die geläufigste Technik ist derzeit, das Cholesteatom in der ersten Sitzung vollständig zu entfernen [8,13,17]. Neben der chirurgischen Behandlung empfehlen einige Autoren eine intraoperative Behandlung mit Kortison nach einem streng festgelegten Schema und sahen insbesondere bei Fisteln der Grade IIb und III deutlich bessere postoperative Ergebnisse [3,12].…”
unclassified
“…The matrix was always removed during the first operation. 15 Controversy remains regarding the optimal management of this condition. Specifically, considerations of intact canal wall versus canal wall down approaches as well as total or incomplete matrix removal remain unsettled.…”
mentioning
confidence: 99%